Neutrophil/lymphocyte and monocyte/lymphocyte indexes as potential predictors of relapse at 1 year after diagnosis of pediatric multiple sclerosis: a single-center, exploratory and proof-of-concept study - Palavra, Filipe; Geria, Leonor; Jorge, André; Marques, Margarida; dos Santos, Constança Soares; Amaral, Joana; Ribeiro, Joana Afonso; Pereira, Cristina; Robalo, Conceição (Frontiers in Neuroscience, 2024)
Introduction: Early identification of patients with a more unfavourable outcome in Multiple Sclerosis (MS) is crucial to optimize individualized treatment. Neutrophil-lymphocyte index (NLI) and monocytelymphocyte index (MLI) have been considered as potential biomarkers for disease prognosis. Our study aims to investigate the usefulness of NLI and MLI as predictors of relapse, disability progression, and lesion accumulation on magnetic resonance imaging (MRI) one year after diagnosis and treatment initiation, in paediatric-onset MS. Methods: A retrospective single-center study was conducted, including patients with diagnosis of MS established in paediatric age (<18 years old), at least one-year of follow-up, and a complete blood count (CBC) performed at diagnosis. We collected the nearest-to-diagnosis NLI and MLI, as well as clinical and imaging variables, at diagnosis and 12 months later. Our cohort was further dichotomized into two groups, based on the presence of relapses. Statistical significance was considered for p <0.05.Results: Eighteen patients (n=18) were included. The relapsing group had higher mean, minimum, and maximum values for both NLI (5.17±5.85, range: 1.57-11.92) and MLI (0.35±0.22, range: 0.19-0.59), compared to the non-relapsing group (2.19±1.63, range: 1.12-7.32 for NLI, and 0.24±0.09, range: 0.14-0.44 for MLI). A higher percentage of patients in the relapsing group had increased NLI (>1.89, 66.7%) and MLI (>0.21, 66.7%) values than those in the non-relapsing group (46.7%). Patients who presented new T2-hyperintense lesions on MRI after one year of follow-up also had higher mean, minimum, and maximum values of both biomarkers. Patients who did not achieve No Evidence of Disease Activity-3 (NEDA-3) state exhibited higher values for both ratios. However, in our sample, no statistically significant correlations were found between MLI and NLI values and the clinical and imaging variables considered.The ease of obtaining NLI and MLI from routine blood tests renders them useful biomarkers as a screening tool in longitudinal follow-up. Our study was based on a very small sample size, but it allowed us to verify the feasibility of the protocol used. It is intended to involve other centers in the next phase of this work, testing the possible usefulness of the indices under analysis on a larger sample.